Mengintegrasikan Seni dan Budaya Lokal dalam Pembelajaran SD untuk Meningkatkan Identitas Nasional - Petri Jewitan Hulu; Khailan Zariah; Yarnati Hulu (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This research uses a qualitative method aimed at examining how the integration of local arts and culture into elementary school learning can enhance students’ national identity. In the rapid era of globalization, preserving local culture becomes essential as a foundation in shaping the nation’s character. Through a case study approach in several elementary schools in Indonesia, it was found that incorporating elements of traditional arts such as dance, regional music, folklore, and local crafts into subjects like Indonesian Language, Arts and Culture, and Civics Education had a positive impact on students’ understanding and appreciation of their cultural heritage. Teachers act as creative facilitators by connecting lesson materials with local wisdom, making the learning process more meaningful and contextual. The results show that students become more proud of their own culture, develop a stronger sense of historical awareness, and foster a deeper love for their country. Therefore, integrating local arts and culture not only enriches the learning process but also serves as an effective strategy in building national identity from an early age.